2011
DOI: 10.1088/0004-637x/727/2/114
|View full text |Cite
|
Sign up to set email alerts
|

THE BALLOON-BORNE LARGE APERTURE SUBMILLIMETER TELESCOPE (BLAST) 2005: A 10 deg2SURVEY OF STAR FORMATION IN CYGNUS X

Abstract: We present Cygnus X in a new multi-wavelength perspective based on an unbiased BLAST survey at 250, 350, and 500 μm, combined with rich data sets for this well-studied region. Our primary goal is to investigate the early stages of high-mass star formation. We have detected 184 compact sources in various stages of evolution across all three BLAST bands. From their well-constrained spectral energy distributions, we obtain the physical properties mass, surface density, bolometric luminosity, and dust temperature.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 94 publications
(292 reference statements)
2
30
2
1
Order By: Relevance
“…In this paper we adopt a recent distance estimate of 1.61 kpc, obtained from maser astrometry . This is consistent with the adopted values in recent studies of the Cygnus region (Schneider et al 2006;Roy et al 2011). Based on its luminosity and IRAS colours, IRAS 20286+4105 has been proposed as a candidate highmass protostellar object (Molinari et al 1996).…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this paper we adopt a recent distance estimate of 1.61 kpc, obtained from maser astrometry . This is consistent with the adopted values in recent studies of the Cygnus region (Schneider et al 2006;Roy et al 2011). Based on its luminosity and IRAS colours, IRAS 20286+4105 has been proposed as a candidate highmass protostellar object (Molinari et al 1996).…”
Section: Introductionsupporting
confidence: 91%
“…In the FIR, this region has been studied in detail by Verma et al (2003) at 150 and 210 µm using the balloon-borne TIFR telescope. IRAS 20286+4105 also forms part of the Balloonborne Large Aperture Submillimeter Telescope (BLAST) survey of the Cygnus region at 250, 350 and 500 µm (Roy et al 2011). Based on the near-infrared (NIR) H2 line maps, Varricatt et al (2010) have identified two outflows, the positions of which are consistent with the CO outflow results of Zhang et al (2005).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations